China's left-behind children : caretaking, parenting, and struggles - Chen, Xiaojin (New Brunswick : Rutgers University Press, 2024)
"The unprecedented rural-to-urban migration in China over the past three decades has placed the social phenomenon of "left-behind children" at the forefront of sociological inquiry. One unintended consequence of this mass migration is the exponentially increased size of left-behind children-children whose parents migrated to more developed areas and who live with one parent or other extended family members. The daily lives of these children, including caretaking arrangement, parent-child bonding and communication, and schooling, are fraught with distractions and uncertainties. Paying special attention to this marginalized group, this book investigates shaping family dynamics and children's general wellbeing, including school performance, delinquency, resilience, feelings of ambiguous loss, and other psychological problems. Blending theory, empirical research, and real-world interviews with left-behind children, China's Left Behind Children provides a uniquely close look at these children's lives while also providing the larger national context that defines and shapes their everyday lives"--
Frontmatter -- CONTENTS -- List of Illustrations -- 1 Introduction -- 2 Who Leaves and Who Stays? Factors Associated with Parental Migration and Caretaking Arrangements -- 3 Caretaking at Home: Grandparenting and One-Parent Caretaking -- 4 Parenting from Afar: Long-Distance Parenting and Short Visits -- 5 "Have You Finished Your Homework?": Parental Migration, Caretaking Practices, and Children's Schooling -- 6 Are Left-Behind Children More Deviance-and Delinquency-Prone? -- 7 Children's Psychological Well-Being: Caretaking Practices, Long-Distance Parenting, and Ambiguous Loss -- 8 Conclusion -- Acknowledgments -- References -- Index -- ABOUT THE AUTHOR
Includes bibliographical references and index.
Description based on print version record.
JSTOR
Keywords: Children -- China -- Social conditions; Children of single parents -- China; Rural-urban migration -- China; Enfants -- Chine -- Conditions sociales; Enfants de famille monoparentale -- Chine; Exode rural -- Chine; SOCIAL SCIENCE / General; Children of single parents; Children -- Social conditions; Rural-urban migration; China